2002
DOI: 10.1139/v02-162
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic binding studies of cell surface carbohydrate epitopes to galectins-1, -3, and -7: Evidence for differential binding specificities

Abstract: Binding of a series of sialylated and non-sialylated cell surface carbohydrates to bovine heart galectin-1, recombinant murine galectin-3, and recombinant human galectin-7 was investigated by isothermal titration microcalori metry (ITC) and hemagglutination inhibition measurements. Galectin-7 shows nearly equal affinities for lactose and Galbeta(1–4)GlcNAc (LacNAc-II). Galectin-7, however, displays six- and 11-fold weaker affinity for LacNAc-II compared with galectins-1 and -3, respectively. The affinity of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 39 publications
7
91
0
Order By: Relevance
“…Our analysis flanked by positive controls revealed an indistinguishable behavior of galectin-7 relative to homodimeric galectin-1. This result can completely be reconciled with the similar potency of both galectins in haemagglutination of trypsinized and glutaraldehyde-fixed rabbit erythrocytes, a hallmark of di-and oligovalent carbohydrate-binding proteins Ahmad et al, 2002). Multivalency effects noted in inhibition assays with branched Nglycans are in line with the detected consequences of aggregation processes in the presence of an excess of glycodendrimers in nano-ESI mass spectrometry.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our analysis flanked by positive controls revealed an indistinguishable behavior of galectin-7 relative to homodimeric galectin-1. This result can completely be reconciled with the similar potency of both galectins in haemagglutination of trypsinized and glutaraldehyde-fixed rabbit erythrocytes, a hallmark of di-and oligovalent carbohydrate-binding proteins Ahmad et al, 2002). Multivalency effects noted in inhibition assays with branched Nglycans are in line with the detected consequences of aggregation processes in the presence of an excess of glycodendrimers in nano-ESI mass spectrometry.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast to galectin-1 homing in on nonreducing terminal Lac/LacNAc units, galectin-7 (and also galectin-3) recognize both terminal and internal ligand sites (Ahmad et al, 2002). In the case of the GM 1 pentasaccharide, the tested galectins bound to the matrix-immobilized ligand in a very similar manner.…”
Section: Discussionmentioning
confidence: 93%
“…Neuropilin-1, a receptor for the guidance cue semaphorin3A, regulates dendritic branching (Morita et al, 2006), and a glycoform has been identified recently as a galectin-1 ligand (Hsieh et al, 2008). Considering that Gal-1 and Gal-3 display common affinities for -galactosides including ganglioside GM1 and the N-glycans of asialofetuin (Ahmad et al, 2002;André et al, 2005;Dam et al, 2005;Hirabayashi et al, 2002), neuropilin-1 appears to be a suitable candidate to mediate the induction of branching by bound pGal-3. However, no evidence for an interaction between pGal-3 and neuropilin was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3, which tolerates a2,6-sialylation in poly(N-acetyllactosamine) chains (44), strongly bound to such cells. But it failed to be discriminatory on the level of cell staining, regardless of the presence or absence of the collagenase-sensitive stalk, which is involved in pentamerization (45).…”
Section: Discussionmentioning
confidence: 99%